Bacterial Imprinting Methods and Their Applications: An Overview. (3rd October 2021) - Zaidi, Shabi Abbas
Abstract: Microbial contaminations and infections are hazardous and pose crucial concerns for humans. They result in severe morbidity and mortality around the globe. Even though dish-culturing, polymerase chain reaction (PCR), an enzyme-linked immunosorbent assay (ELISA) exhibits accurate and reliable detection of bacteria but these methods are time-consuming, laborious, and expensive. This warrants early detection and quantification of bacteria for timely diagnosis and treatment. Bacteria imprinting ensures a solution for selective and early detection of bacteria by snagging them inside their imprinted cavities. This review provides an insight into MIPs based bacterial detection strategies, challenges, and future perspectives. Graphical Abstract: UF0001